2008
DOI: 10.1016/j.jcrs.2007.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the keratometric index: Evaluation by the Pentacam rotating Scheimpflug camera

Abstract: Using the Pentacam-derived keratometric index improved the prediction accuracies of total and posterior corneal powers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 33 publications
7
90
3
4
Order By: Relevance
“…In the literature, the ratio of the radius of the anterior corneal curvature to the radius of the posterior corneal curvature (the AP ratio) ranged from 1.132 (the Gullstrand schematic eye model) to 1.235 in the data from Dubbelman et al 24 With the Pentacam, a normal distribution was observed for most of the corneal parameters, and 1.223 was measured at the central 4.0-mm corneal zone for the AP ratio. 22 Monatalbán et al 25 reported an AP ratio of 1.19 with the Pentacam, which is smaller than that for our data (1.217). They showed that a significant, positive correlation existed between the AP shape factor (defined as 1+asphericity) ratio and age, as between the curvatures of the anterior, posterior corneal surfaces and age at 4.5-and 8.0-mm corneal diameters.…”
Section: Discussioncontrasting
confidence: 82%
“…In the literature, the ratio of the radius of the anterior corneal curvature to the radius of the posterior corneal curvature (the AP ratio) ranged from 1.132 (the Gullstrand schematic eye model) to 1.235 in the data from Dubbelman et al 24 With the Pentacam, a normal distribution was observed for most of the corneal parameters, and 1.223 was measured at the central 4.0-mm corneal zone for the AP ratio. 22 Monatalbán et al 25 reported an AP ratio of 1.19 with the Pentacam, which is smaller than that for our data (1.217). They showed that a significant, positive correlation existed between the AP shape factor (defined as 1+asphericity) ratio and age, as between the curvatures of the anterior, posterior corneal surfaces and age at 4.5-and 8.0-mm corneal diameters.…”
Section: Discussioncontrasting
confidence: 82%
“…In peer-reviewed papers, the reported percentage of patients achieving an UDVA better than 20/40 after toric IOL implantation ranges from 70% to 100% (4,5,32,33) . Spectacle-independence for distance vision was reported by 60% to 85% of patients with unilateral toric IOL (3,6,31,34) and by 69% to 97% of patients with bilateral toric IOLs (7,8,35,36) . Reported percentages of patients with residual refractive astigmatism lower than 0.50 D range from 25% to 100% (9,10,37,38) .…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…This feature is of particular interest in keratoconus, where the corneal thickness varies with a non-linear pattern from the center to the periphery of the cornea. The keratometric index is refined with elevation topographs (Ho et al, 2008). Moreover, where keratometers assume that keratometry derives from a constant corneal refractive power, elevation topographs measures the true power of the cornea (Eryildirim et al, 1994).…”
Section: Topography-based Keratometrymentioning
confidence: 99%